ANALISIS PENILAIAN KINERJA DOSEN MENGGUNAKAN METODE ADAPTIVE NEURON-FUZZY INFERENCE SYSTEM (ANFIS) - Rut Ronauli Hutagaol; Aida Elda Afriza; Mohammad Irfan Fahmi (Politeknik Bisnis Indonesia, 2024)
This research examines the performance of lecturers at Universitas Prima Indonesia using the Adaptive Neuro-Fuzzy Inference System (ANFIS) method to evaluate and enhance teaching quality. The research employs a quantitative approach, collecting data through observations, literature reviews, and questionnaires distributed to 100 students from the Faculty of Science and Technology. Four input variables used are pedagogical competence, professional competence, personal competence, and social competence. The collected data is analyzed using Matlab with ANFIS, which combines the capabilities of artificial neural networks and fuzzy logic to produce accurate predictions. The analysis results show that the ANFIS method is effective in measuring lecturer performance, with high validation results and low error rates. The ANFIS simulation indicates that the majority of lecturers fall into the